Status report - Childhood overweight and obesity in Canada: an integrative assessment - Deepa P. Rao; Erin Kropac; Minh T. Do; Karen C. Roberts; Gayatri C. Jayaraman (Health Promotion and Chronic Disease Prevention in Canada, 2017)
Introduction: Obesity is a complex risk factor for chronic disease that is associated with a number of socioecological determinants. In this status report, we provide an overview of the socioecological framework that is now guiding our ongoing surveillance efforts in the area of childhood overweight and obesity. This framework considers individual risk and protective factors (sociodemographic, lifestyle, psychosocial and early-life) through the lens of the life stage, levels of influence and environments in which these factors play a role. Methods: Using data from the Canadian Community Health Survey and the Canadian Health Measures Survey, univariate and bivariate analyses were used to report on behavioural, psychosocial, and early life factors associated with excess weight among Canadian children. Results: Estimates of early-life (e.g. breastfeeding), behavioural (e.g. physical activity), and psychosocial factors (e.g. sense of community) are presented as they relate to age group, sex, income adequacy and weight status. Conclusion: Building upon our recent reporting on trends in and sociodemographic factors associated with childhood obesity in Canada, this work illustrates the remaining risk and protective factors shown in our surveillance framework. This analysis supports the shift towards a holistic appraisal of determinants related to healthy weights.